The Faraday Effect Tracker of Coronal and Heliospheric Structures (FETCH) instrument - Jensen, Elizabeth A.; Gopalswamy, Nat; Wilson, Lynn B.; Jian, Lan K.; Fung, Shing F.; Nieves-Chinchilla, Teresa; Shelton, Marta; Li, Lihua; Deshpande, Manohar; Purves, Lloyd; Lazio, Joseph; Manchester, Ward B.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
There continues to be open questions regarding the solar wind and coronal mass ejections (CMEs). For example: How do magnetic fields within CMEs and corotating/stream interaction regions (CIRs/SIRs) evolve in the inner heliosphere? What is the radially distributed magnetic profile of shock-driving CMEs? What is the internal magnetic structure of CMEs that cause magnetic storms? It is clear that these questions involve the magnetic configurations of the solar wind and transient interplanetary plasma structures, for which we have limited knowledge. In order to better understand the origin of the magnetic field variability in steady state structures and transient events, it is necessary to probe the magnetic field in Earth-directed structures/disturbances. This is the goal of the Multiview Observatory for Solar and Terrestrial science (MOST) mission. For MOST to answer the above questions, we propose the instrument concept of the Faraday Effect Tracker of Coronal and Heliospheric structures (FETCH), a simultaneous quad-line-of-sight polarization radio remote sensing instrument. With FETCH, spacecraft radio beams passing through the Sun-Earth line offer the possibility of obtaining information of the plasma conditions via analysis of radio propagation effects such as Faraday rotation and wave dispersion, which provide inform us of magnetic field and total electron content (TEC). This is the goal of the FETCH instrument, one of ten instruments proposed to be hosted on the MOST mission. The MOST mission will provide an unprecedented opportunity to achieve NASA’s Heliophysics Science Goal to “Explore and characterize the physical processes in the space environment from the Sun”.